STRATEGI MENINGKATKAN ABSORPTIVE CAPACITY PERUSAHAAN: (Studi Empiris pada Perusahan Jasa Konstruksi Skala Kecil dan Menengah di Banten) - Sanusi, Fauji; Ganika, Gerry (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2021)
In general, small and medium enterprises (SMEs) facing difficulties in increasing competitiveness in the industry. Several studies have stated that the contributing factor lies in the poor quality of human resources, especially related to knowledge and labor skills. Absorptive capacity is the ability to absorb information into knowledge and skills. Therefore, this study aims to obtain empirical evidence related the efforts to increase absorptive capacity in 74 construction companies in Banten Province. The results of the analysis show that intellectual stimulation can increase the absorptive capacity positively and significantly. Meanwhile, explicit knowledge sharing is not empirically proven affected absorptive capacity.